Cognitive and gait in Wilson’s disease: a cognitive and motor dual-task study - Wang, Gongqiang; Jin, Ping; Ma, Xinfeng; Hong, Xia; Zhang, Long; Lin, Kang; Wen, Xiao; Bai, Xue; Han, Yongzhu (Frontiers in Neurology, 2023)
Background Cognitive and motor dual-tasks play important roles in daily life. Dual-task interference impacting gait performance has been observed not only in healthy subjects but also in subjects with neurological disorders. Approximately 44–75% of Wilson’s disease (WD) patients have gait disturbance. According to our earlier research, 59.7% of WD patients have cognitive impairment. However, there are few studies on how cognition affects the gait in WD. Therefore, this study aims to explore the influence of cognitive impairment on gait and its neural mechanism in WD patients and to provide evidence for the clinical intervention of gait disturbance. Methods We recruited 63 patients who were divided into two groups based on their scores on the Addenbrooke’s cognitive examination III (ACE-III) scale: a non-cognitive impairment group and a cognitive impairment group. In addition to performing the timed up and go (TUG) single task and the cognitive and motor dual-task digital calculation and animal naming tests, the Tinetti Balance and Gait Assessment (POMA), Berg Balance Scale (BBS), and brain MRI severity scale of WD (bMRIsc-WD) were evaluated. The dual-task cost (DTC) was also computed. Between the two groups, the results of the enhanced POMA, BBS, and bMRIsc-WD scales, as well as gait performance measures such as TUG step size, pace speed, pace frequency, and DTC value, were compared. Results (1) Among the 63 patients with WD, 30 (47.6%) patients had gait disturbance, and the single task TUG time was more than 10 s. A total of 43 patients had cognitive impairment, the incidence rate is 44.4%. Furthermore, 28 (44.4%) patients had cognitive impairment, 39 (61.9%) patients had abnormal brain MRI. (2) The Tinetti gait balance scale and Berg balance scale scores of patients with cognitive impairment were lower than those of patients without cognitive impairment (p < 0.05), and the pace, step size, and pace frequency in the single task TUG were slower than those of patients without cognitive impairment (p < 0.05). There was no change in the pace frequency between the dual-task TUG and the non-cognitive impairment group, but the pace speed and step size in the dual-task TUG were smaller than non-cognitive impairment group (p < 0.05). There was no difference in DTC values between cognitive impairment group and non-cognitive impairment group when performing dt-TUG number calculation and animal naming respectively (p > 0.05). However, regardless of cognitive impairment or not, the DTC2 values of number calculation tasks is higher than DTC1 of animal naming tasks in dt-TUG (p < 0.05). (3) Pace speed and step size were related to the total cognitive score, memory, language fluency, language understanding, and visual space factor score of the ACE-III (p < 0.05), and step frequency was correlated with memory and language comprehension factors (p < 0.05). There was no correlation between the attention factor scores of the ACE-III and TUG gait parameters of different tasks (p > 0.05). Brain atrophy, the thalamus, caudate nucleus, and cerebellum were correlated with cognitive impairment (p < 0.05), the lenticular nucleus was related to the step size, brain atrophy was related to the pace speed, and the thalamus, caudate nucleus, and midbrain were involved in step frequency in WD patients (p < 0.05). Conclusion WD patients had a high incidence of cognitive impairment and gait disorder, the pace speed and step size can reflect the cognitive impairment of WD patients, cognitive impairment affects the gait disorder of WD patients, and the different cognitive and motor dual-tasks were involved in affecting gait parameters. The joint participation of cognitive impairment and lesion brain area may be the principal neural mechanism of gait abnormality in WD patients.